2019
DOI: 10.1002/mnfr.201900262
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharides Protect against Necrotizing Enterocolitis by Inhibiting Intestinal Damage via Increasing the Proliferation of Crypt Cells

Abstract: Scope: Necrotizing enterocolitis (NEC) is a devastating disease that is highly lethal in premature infants. Human milk oligosaccharides (HMOs) efficiently reduce the incidence of NEC. However, the protective mechanism of HMO treatment is unknown. It is hypothesized that HMOs protect against NEC by inhibiting the damage to intestinal epithelial cells. Methods and results: C57BL/6 pups are challenged with hypoxia and cold stress to induce NEC. All pups are sacrificed after 72 h. It is found that HMO administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 52 publications
1
57
0
Order By: Relevance
“…The key results of previous studies in this field need to be discussed. Some studies found that colostrum was effective in reducing the rate of NEC, revealing its effect in building up immunity [11,[39][40][41][42]. Term babies could suck their mothers' nipples to obtain breast milk and their immunity would be triggered through the first bite with colostrum being served as stimulator [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…The key results of previous studies in this field need to be discussed. Some studies found that colostrum was effective in reducing the rate of NEC, revealing its effect in building up immunity [11,[39][40][41][42]. Term babies could suck their mothers' nipples to obtain breast milk and their immunity would be triggered through the first bite with colostrum being served as stimulator [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…The human milk oligosaccharides (HMOs) select the growth of commensals such as Bifidobacteria and prevent the growth of potential pathogens such as Clostridium difficile [41,42]. Moreover, HMOs enhance overall barrier integrity by making enterocytes less vulnerable to bacterial-induced innate immunity [43]. Therefore, breast-feeding seems to be ideal for the engraftment of a symbiotic gut microbiome.…”
Section: Microbiome Environmental Factors and Gut Inflammation: Imentioning
confidence: 99%
“…The NEC model was developed as described by Wang et al [ 16 ]. On the first day after birth, nine SPF class Sprague-Dawley rat pups were used, including three in the control group and six in the NEC model group.…”
Section: Methodsmentioning
confidence: 99%